HIC1 loss promotes prostate cancer metastasis by triggering epithelial–mesenchymal transition. Issue 4 (13th June 2017) - Hao, Mingang; Li, Yue; Wang, Jinglong; Qin, Jun; Wang, Yingying; Ding, Yufeng; Jiang, Min; Sun, Xueqing; Zu, Lidong; Chang, Kun; Lin, Guowen; Du, Jiangyuan; et al.
Abstract: Metastatic disease is the leading cause of death due to prostate cancer (PCa). Although the hypermethylated in cancer 1 (HIC1) gene has been observed to be epigenetically modified in PCa, its intrinsic role and mechanism in PCa metastasis still remain uncertain. Here, we show that hypermethylation of the HIC1 promoter markedly reduces its suppressive function in metastatic PCa tissues as compared with primary and adjacent normal prostate tissues, and is associated with poor patient survival. PCas in cancer‐prone mice homozygous for a prostate‐targeted Hic1 conditional knockout showed stronger metastatic behaviour than those in heterozygous mice, as a result of epithelial–mesenchymal transition (EMT). Moreover, impairment of HIC1 expression in PCa cells induced their migration and metastasis through EMT, by enhancing expression of Slug and CXCR4, both of which are critical to PCa metastasis; the CXCL12–CXCR4 axis promotes EMT by activating the extracellular signal‐regulated kinase (ERK) 1/2 pathway. Taken together, our results suggest that evaluation of HIC1–CXCR4–Slug signalling may provide a potential predictor for PCa aggressiveness. Copyright © 2017 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.